Getting Ready for Fifth Grade - Conklin, Wendy (Summer Blast Ser., 2016)
Prevent learning loss and prepare students for fifth grade with fun theme-based units including language arts, mathematics, and critical and creative thinking activities. Support parents with everyday learning ideas and a handbook about today's standards.